Sago-Based Food Product Creation Training To Increase Competitiveness In The Market In Ngenang Island - Rosie Oktavia Puspita Rini; Afriani, Miratia; Mikasari, Dewi Aurora; Santika, Kamelia; Sihombing, Hans Steven (JURNAL KEKER WISATA, 2025)
Community service with the topic "Training on the Creation of Sago-Based Food Products to Increase Competitiveness in the Market on Ngenang Island" aims to increase the community's skills and knowledge in using sago as an innovative food raw material. This activity aims to improve the local economy, encourage the emergence of new entrepreneurs in the sago-based culinary sector, and preserve local wisdom related to food. In this activity, the community is trained to process sago into food products that have added value, with innovations in aspects of taste, appearance and packaging that can compete in local and regional markets. It is hoped that the implementation of this activity can contribute to increasing the competitiveness of local products, the economic welfare of the community, and preserving the tradition of using sago on Ngenang Island. Apart from that, this activity also provides benefits for educational institutions by increasing credibility in community service and opening up opportunities for research collaboration. The impact for the government includes improving the regional economy, food security and preserving local culture.